Challenges in nurturing HFASD teens: Emotional crises and expectations of mothers in Malaysia - Mohd Fazree, Shima Dyana; Aun, Nur Saadah Mohamad; Zakaria, Siti Marziah; Badayai, Abdul Rahman Ahmad; Daud, Tuti Iryani Mohd; Idris, Idayu Badilla (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
The transition to young adulthood brings distinctive challenges for high-functioning autism spectrum disorder (HFASD) children and their families, especially post-formal education. This qualitative case study research aims to explore hurdles faced by mothers navigating HFASD adolescents. The result shows that financial strain, stigma, and loneliness loom large, compounded by emotional crises tied to uncertainty and stress about their children's future. Mothers advocate for multiple work opportunities and independence, underscoring a notable gap between HFASD teens' needs, available services, and community resources. The study enlightened mothers and inspired proactive measures, emphasizing the imperative for a collective, interdisciplinary effort to align services comprehensively—addressing residential, employment, and social aspects—to enhance the quality of life for HFASD individuals.